Exergetic and exergoeconomic assessments of a diesel engine fuelled with waste chicken fat biodiesel-diesel blends - Gad, M. S.; Uysal, Cuneyt; El-Shafay, A. S.; Agbulut, Uemit (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Researchers have constantly been looking for renewable alternative fuels due to high fuel price volatility, energy security concerns, and produced harmful emissions. One of the promising alternatives is to produce biodiesel from waste economical feedstock such as chicken fat. Esterification and transesterification are used to create methyl ester from chicken fat. Then, 25%, 50%, 75%, and 100% of chicken oil biodiesel are volumetrically blended with diesel fuel. Diesel engine is loaded between 0% and 100% at 3000 rpm rated speed. Exergetic and exergoeconomic assessments of diesel engine fuelling with blends of chicken biodiesel were conducted in the present study. Diesel oil performed most efficiently in terms of exergy. For B100, the worst exergetic results are attained. The exergy efficiency of test engine at 75% engine load was 33.25% for the D100 and 27.85% for the B100. D100 produced the best exergoeconomic findings, while adding biodiesel to D100 made the exergoeconomic parameters worse. Crankshaft work had a particular exergy cost of 110.02 $/GJ for D100 and 194.37 $/GJ for B100 at 75% of engine output power. In the conclusion, it is noted that the waste chicken fat methyl ester can be used at low fractions as a substitute for traditional diesel fuel without modifying the engine, and this is a promising solution for waste management, turning waste products into an energy source, and dwindling fossil fuel reserves.
Keywords: Animal fat; Exergoeconomics; Exergy; Sustainability; Waste to energy; PERFORMANCE; COMBUSTION; EMISSIONS; FEEDSTOCKS; Thermodynamics; Energy & Fuels